Reduction of ammonia volatilization through mixing urea with humic and fulvic acids isolated from palm oil mill effluent sludge - Shamsuddin, Rosliza; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad; Jalloh, Mohamadu Boyie (Science Publications, 2009)
Problem statement: Ammonia volatilization from surface-applied urea may be substantial but it is possible to control it by mixing urea with acidic substances such as Humic Acids (HA) and Fulvic Acids (FA). The objective of this study was to compare the effects of urea-HA, urea-FA, urea-acidified (HA+FA) mixtures on ammonia loss, soil pH, soil exchangeable ammonium and available nitrate accumulation compared to urea alone. Approach: The effects of urea amended with or without HA and FA were evaluated in a laboratory condition using a closed-dynamic air flow system. Ammonia loss, soil pH, soil exchangeable ammonium and available nitrate were determined using standard procedures. Results: Humic acid alone was not effective in controlling ammonia volatilization even though ammonium retention was found to be significantly higher compared to urea alone. Fulvic acid significantly reduced ammonia volatilization by 50% compared to urea alone. It also caused the highest retention of soil exchangeable ammonium and available nitrate. However, there was no ammonia volatilization with acidified HA and FA. Ammonium and nitrate accumulation for FA was better than acidified HA and FA. Ammonia loss could be reduced by improving ammonium retention. It must be stressed that results obtained in the incubation experiment using an acidic (pH water 6.32) soil of Typic Paleudults (Bekenu series) may only be applicable to similar acid soils. Conclusion: Urea amended with HA or HA and FA significantly reduced ammonia loss. The outcome of this study might be contributed to the improvement of urea N use efficiency as well as reducing environmental pollution.